1997
DOI: 10.1007/s004250050171
|View full text |Cite
|
Sign up to set email alerts
|

Induction of genes encoding plastidic phosphorylase from spinach ( Spinacia oleracea L.) and potato ( Solanum tuberosum L.) by exogenously supplied carbohydrates in excised leaf discs

Abstract: A full-length cDNA encoding plastidic phosphorylase (Pho1, EC 2.4.1.1) from spinach (Spinacia oleracea L.) has been isolated. Analysis of the deduced protein sequence revealed considerable homologies with the corresponding proteins from other plants, animals and prokaryotes. Escherichia coli cells carrying the entire cDNA for Pho1 expressed an active phosphorylase, which resembled the properties of the plastidic isozyme of spinach with respect to its low affinity to glycogen. Expression of Pho1 was studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…On the other hand, STP itself may also be involved in starch synthesis [6], and in this case, both enzymes would form starch in the direct neighbour hood of the vascular tissue. Duwenig et al [24] reported parallels in the regulation of expression of phosphorylase and AGPase genes in spinach and pota toes and use this finding to support their suggestion that STP is involved in starch synthesis. However, such evidence can equally well indicate that STP partici pates in starch cycling.…”
Section: Agpase Gene Promoter Expressionmentioning
confidence: 54%
See 1 more Smart Citation
“…On the other hand, STP itself may also be involved in starch synthesis [6], and in this case, both enzymes would form starch in the direct neighbour hood of the vascular tissue. Duwenig et al [24] reported parallels in the regulation of expression of phosphorylase and AGPase genes in spinach and pota toes and use this finding to support their suggestion that STP is involved in starch synthesis. However, such evidence can equally well indicate that STP partici pates in starch cycling.…”
Section: Agpase Gene Promoter Expressionmentioning
confidence: 54%
“…However, such evidence can equally well indicate that STP partici pates in starch cycling. If it is so, such cycling is likely to involve the plastid isoform of STP, since Duwenig et al [24] presented evidence that the cytosolic isoform was not involved in starch breakdown during storage. One may then hypothesize that amylases degrade starch in storage parenchyma cells, the resulting sugars being transported towards the vascular tissue, and starch is resynthesized around the vascular tissue.…”
Section: Agpase Gene Promoter Expressionmentioning
confidence: 96%
“…The other type, Pho2 (or,previously,Pho H), is restricted to the cytosol and possesses an extremely high anity towards branched polyglucans such as glycogen (Steup 1988). Plant Pho1-type phosphorylases are unique in two aspects: First, all ®ve proteins of this type sequenced so far contain a large insertion of approximately 80 amino acid residues that is located between the C-terminal and the N-terminal domain (Nakano and Fukui 1986;Lin et al 1990;Sonnewald et al 1995;Buchner et al 1996;Duwenig et al 1997). The insertion has not been found in any phosphorylase from bacteria or animals (Newgard et al 1989) or in the plant Pho2-type enzymes (Mori et al 1991;Buchner et al 1996).…”
Section: Introductionmentioning
confidence: 94%
“…In potato leaf discs, expression both of the Pho1a-type phosphorylase and of ADPglucose pyrophosphorylase is induced by exogenous sugars such as sucrose or glucose (Duwenig et al 1997).…”
Section: Fig 5a±dmentioning
confidence: 99%
“…However, observations have shown that the accumulation of starch is connected with the increase of SP activity in potato tubers (Mingo-Castel et al 1976;Albrecht et al 2001), maize endosperm (Liu and Shannon 1981), rice (Baun et al 1970), wheat (Schupp and Ziegler 2004), and sweet potato roots (Chang et al 2000). Starch content is also in proportion to the expression of SP in potato (Brisson et al 1989;St-Pierre and Brisson 1995;Duwenig et al 1997;Albrecht et al 2001), spinach (Duwenig et al 1997), and pea (Van Berkel et al 1991). We have reported that the proteolytic modification of L-SP on L78 has a regulatory role for its catalytic behavior (Chen et al 2002).…”
Section: Introductionmentioning
confidence: 95%